ANALISIS KELAYAKAN PENGEMBANGAN KAWASAN INDUSTRI PERIKANAN PELABUHAN PERIKANAN SAMUDERA KENDARI - Arifin Safari; Andi Irwan Nur; Muh. Ramli (Universitas Halu Oleo, 2019)
Land is a limited and non-renewable resource, while the number of people who need land for their activities continues to increase over time. Concentration of human activities for various activities in an area because most of human life depends on land that can be used as a source of livelihood. One of them is the use of land as an industrial area. Industrial development in urban areas raises new problems for urban areas, especially for land use, namely the occurrence of land use changes that are not in accordance with the allotment. Therefore, to anticipate future land use deviations, the existing conditions of land use need to be identified and analyze the suitability of industrial land in the PPS Kendari Area. The research method used in this research is descriptive method with a qualitative approach. The data analysis method used is the Overlay analysis technique by utilizing ArcGis software. From the results of the analysis of the suitability of industrial land based on the Existing Condition, it was found that land of 7.82 Ha was said to be appropriate as an industrial estate development. Keywords: Land, Fisheries Industry, Feasibility